2000
DOI: 10.1080/01904160009382062
|View full text |Cite
|
Sign up to set email alerts
|

Cotton growth and boron distribution in the plant as affected by a temporary deficiency of boron

Abstract: The knowledge of nutrient mobility is an important tool to define the best fertilizer management and diagnosis techniques. Patterns of boron (B) mobility in plants have been reviewed, but there is very little information on B distribution and mobility in cotton. An experiment was conducted to study plant growth and B distribution in cotton when the nutrient was applied in the nutrient solution or to the leaves, and when a temporary deficiency was imposed. Cotton (Gossypium hirsutum, Latifolia, cv. IAC 22) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
2
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 23 publications
1
26
2
5
Order By: Relevance
“…Here, B was incorporated into cell walls, probably bound to Ca, and was unavailable for the regular formation of new vascular tissue (Figures 2 and 4). Rosolem & Costa (2000) observed that a temporary B deficiency seems to cause a permanent damage to cotton plants, once there was no full growth recovery when B was replaced in nutrient solution. This was attributed to xylem malformation in the deficiency period (Robertson & Loughman, 1974) what seems to be the case in this experiment with coffee as well.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, B was incorporated into cell walls, probably bound to Ca, and was unavailable for the regular formation of new vascular tissue (Figures 2 and 4). Rosolem & Costa (2000) observed that a temporary B deficiency seems to cause a permanent damage to cotton plants, once there was no full growth recovery when B was replaced in nutrient solution. This was attributed to xylem malformation in the deficiency period (Robertson & Loughman, 1974) what seems to be the case in this experiment with coffee as well.…”
Section: Resultsmentioning
confidence: 99%
“…Cotton shoot dry matter yields, plant height and flower and fruit set were reduced by a temporary B deficiency, which could not be prevented by foliar application of B (Rosolem & Costa, 2000). The authors hypothesized that temporary B deficiency in a plant that does not retranslocate B causes permanent damage, once growth was not fully recovered after replacing B in the nutrient solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apesar de Rosolem & Costa (2000) constatarem que o B, aplicado por via foliar no algodoeiro, não é translocado do local de aplicação para as demais partes da planta, denotando uma mobilidade restrita desse nutriente nestas plantas, Carvalho et al (1996) obtiveram aumentos de produtividade de algodão com aplicações foliares de B. Bevilaqua et al (2002) também afirmam que a aplicação foliar de B pode aumentar o número de vagens e a massa de sementes por planta, quando realizada na fase de floração.…”
Section: Resultsunclassified
“…Boron participates in cell wall formation (Brown et al, 2002), cell division and elongation (Goldbach et al, 2001;Oliveira et al, 2006), membrane function (Zhao and Oosterhuis, 2003) and carbohydrate metabolism and transport (Zhao and Oosterhuis, 2002;Sheng et al, 2009). Boron deficiency causes a rapid inhibition of plant growth and was believed to have low phloem mobility (Rosolem and Costa, 2000). Although B mobility has been demonstrated in some species (Brown et al, 2002), its role remains controversial (Shaaban, 2010).…”
Section: Introductionmentioning
confidence: 99%